Modeling of power propagation at coupling region for a slightly fused coupled fibers - Toto, Saktioto (2007)

(untitled)
Coupled fibers are successfully fabricated by injecting hydrogen flow at 1bar and fused slightly by unstable torch flame in the range of 800-1350oC. Coupling coefficient and refractive index are estimated from the experimental result of the coupling ratio distribution from 1% to 75%. The change of structural and geometrical fiber affects the normalized frequency (V) even for single mode fibers. Coupling ratio changes V at coupling region. Parametric variations are performed on the left and right hand side and center of the coupling region. A partial power is derived using V, normalized lateral phase constant (u), and normalized lateral attenuation constant, (w) through the second kind of modified Bessel function of the l order, which obeys the normal mode, and normalized propagation constant (b). Total power is maintained constant and partial power is integrated through V, u and w over the pulling length range of 7500-9500Î¼m for 1-D where radial and angle directions are ignored. The core radius of fiber significantly affects V and power partially at coupling region rather than wavelength and refractive index of core and cladding. This model has power phenomena in transmission and reflection for industrial application of coupled fibers. Keywords: single mode fiber, coupling ratio, normalized frequency, power